THE CRAVE OF FIXED DOSE COMBINATION IN INDIAN MARKET - J, BALASUBRAMANIAN; N, RADHIKA; AV, BADARINATH (Asian Journal of Pharmaceutical and Clinical Research, 2014)
The aim of the present retrospective works reveals the need of fixed-dose combination (FDC) in Indian market as per the Indian regulations. A combination drug most commonly refers to an FDC, which is a formulation including two or more active pharmaceutical ingredients combined in a single dosage form, which is manufactured and distributed in certain respective fixed doses. This review outlines the FDCs rationale, guidelines on data required for approval for marketing FDCs, marketing potential throughout the world. The safety of the combination drugs has to be thoroughly evaluated, and there are considerations for the drugs that are already in the market as individual or single-drug entity. However, the safety profile of the established drugs will alter when they are combined together. However, many of the irrational combinations are popular and widely prescribed by physicians in our country. This study provides a comprehensive analysis of the current markets for FDC products throughout the world and the market potential of promising drugs under development. Keywords: Fixed dose combinations, Active pharmaceutical ingredients, Human immunodeficiency virus, Chronic obstructive pulmonary disease, World Health Organization, Non-steroidal anti-inflammatory.